2020
DOI: 10.1177/1350507620904307
|View full text |Cite
|
Sign up to set email alerts
|

The power in positionings: A Foucauldian approach to knowledge integration processes

Abstract: This study explores the role of relational power and discursive positioning in the knowledge integration process of an interdisciplinary project developing a steam turbine. As boundaries are an important focus of study for knowledge integration studies, more engagement is needed to not only map boundary work in the knowledge integration process, but also to acknowledge the role of power in this context. With help of governmentality and positioning theory, we show how power struggles are manifested as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 51 publications
(81 reference statements)
0
6
0
Order By: Relevance
“…Second, as seen in Engstrand and Enberg (2020), governing of oneself needs to be investigated further (Dean, 1999; Rose, 1999) in order to understand how individuals act on themselves and with others under this technology (Joshi et al, 2010). The longevity of management-by-generation as a bio-political technology of governance could also be explored in this context analysing what constitutes the long-term side effects of thinking of oneself and others as part of a generation with certain dispositions to work?…”
Section: Resultsmentioning
confidence: 99%
“…Second, as seen in Engstrand and Enberg (2020), governing of oneself needs to be investigated further (Dean, 1999; Rose, 1999) in order to understand how individuals act on themselves and with others under this technology (Joshi et al, 2010). The longevity of management-by-generation as a bio-political technology of governance could also be explored in this context analysing what constitutes the long-term side effects of thinking of oneself and others as part of a generation with certain dispositions to work?…”
Section: Resultsmentioning
confidence: 99%
“…As Jenkins (1996) notes, organisational life typically thrives on the production of internal symbolic distinctions between members and non-members (cf. Engstrand and Enberg, 2020;Hong and O, 2009). These distinctions and divisions are so subtle that they are often missed by outsiders.…”
Section: On Membership Divisions Of Labour and Their Labours Of Divisionmentioning
confidence: 99%
“…Given the presence of multidisciplinary ways of working, knowledge specialization, and the promotion of innovations across organizational sectors, understanding how such power struggles shape knowledge co-creation is of great importance to researchers and practitioners in the fields of management and organization (e.g. Engstrand and Enberg, 2020; Mørk et al, 2008; Oborn and Dawson, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The analysis focuses on ethnographic observations from meetings and qualitative interviews collected over the course of 18 months. Drawing on discursive positioning, I follow in the footsteps of prior studies that have shown how discourse can be used to legitimate knowledge and bring about political effects (Engstrand and Enberg, 2020; Gherardi and Nicolini, 2002a; Grant et al, 1998; Hardy and Phillips, 2004; Heizmann, 2011). I also explore how coercive power contributes to power and knowledge negotiations in knowledge co-creation by enhancing conflicting discursive positioning and preventing the building of coactive power (e.g.…”
Section: Introductionmentioning
confidence: 99%